2009
DOI: 10.1258/ijsa.2008.008401
|View full text |Cite
|
Sign up to set email alerts
|

Loss of correlation between HIV viral load and CD4+ T-cell counts in HIV/HTLV-1 co-infection in treatment naïve Mozambican patients

Abstract: Seven hundred and four HIV-1/2-positive, antiretroviral therapy (ART) naïve patients were screened for HTLV-1 infection. Antibodies to HTLV-1 were found in 32/704 (4.5%) of the patients. Each co-infected individual was matched with two HIV mono-infected patients according to World Health Organization clinical stage, age ±5 years and gender. Key clinical and laboratory characteristics were compared between the two groups. Mono-infected and co-infected patients displayed similar clinical characteristics. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…This value is slightly higher than the 4.1% prevalence of HTLV-I in HIV co-infected patients in Maputo, Mozambique. 9 Although the serologic testing used in the current study did not distinguish between HTLV-I and HTLV-II, worldwide distribution strongly suggests that most infections in this region of southern Africa are HTLV-I, 10 and studies in Mozambique have not found HTLV-II. 11 Apart from tuberculosis, the relation of these co-infections to HIV pathogenesis and progression is largely unknown.…”
Section: Discussionmentioning
confidence: 52%
“…This value is slightly higher than the 4.1% prevalence of HTLV-I in HIV co-infected patients in Maputo, Mozambique. 9 Although the serologic testing used in the current study did not distinguish between HTLV-I and HTLV-II, worldwide distribution strongly suggests that most infections in this region of southern Africa are HTLV-I, 10 and studies in Mozambique have not found HTLV-II. 11 Apart from tuberculosis, the relation of these co-infections to HIV pathogenesis and progression is largely unknown.…”
Section: Discussionmentioning
confidence: 52%
“…A study on 752 individuals attending public heath centers from different areas of this country found a seroprevalence of 2.3% with geographical regional variation (Caterino-de-Araujo et al, 2010). Furthermore, some cases of TSP/HAM have been reported in Mozambique (Engelbrecht et al, 1999) and HTLV-1 infection has been seen at a rate of around 4% in HIV infected patients (Bhatt et al, 2009). The estimation of the number of HTLV-1 infected persons can be done only for Mozambique (Table 2).…”
Section: Htlv-1 Worldwide Distribution and Prevalence Estimates By Gementioning
confidence: 99%
“…[11] What is, however, less controversial and perhaps of greater relevance is the effect of HTLV-1 on T-lymphocytes, and in particular, its association with CD4 + lymphocytosis in HIV-1 co-infected patients. [12,13] [12] A recent study in Mozambique demonstrated that co-infected pre-HAART adult patients were seven times more likely to have CD4 + counts >500 cells/μl (median 525 cells/μl) than HIV mono-infected patients. [13] However, as these CD4 + cells are likely to be functionally altered, associated with a loss of naive cells and a higher activation pattern, CD4 + lymphocyte counts in HIV-1/ HTLV-1 co-infected patients cannot be considered to be a reliable marker of immunological competence.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] [12] A recent study in Mozambique demonstrated that co-infected pre-HAART adult patients were seven times more likely to have CD4 + counts >500 cells/μl (median 525 cells/μl) than HIV mono-infected patients. [13] However, as these CD4 + cells are likely to be functionally altered, associated with a loss of naive cells and a higher activation pattern, CD4 + lymphocyte counts in HIV-1/ HTLV-1 co-infected patients cannot be considered to be a reliable marker of immunological competence. [12] Furthermore, CD4 + counts can be dramatically raised on account of ATLL (i.e.…”
Section: Discussionmentioning
confidence: 99%